Cytoreductive Surgery Plus Hyperthermic Perioperative Chemotherapy for Selected Patients with Peritoneal Metastases from Colorectal Cancer: A New Standard of Care or an Experimental Approach? - Paul H. Sugarbaker (Gastroenterology Research and Practice)
Peritoneal metastases (PM) are a common presentation for patients with metastatic colorectal cancer (CRC), and the median survival of patients with PM is approximately one year. In a majority of patients, the disease remains limited to the peritoneal cavity. Therefore, investigators have applied cytoreductive surgery (CRS) and heated perioperative chemotherapy (HIPEC) as a standard approach for selected patients with PM from CRC. These investigators have demonstrated a very promising long-term survival in a subset of patients with a limited amount of isolated peritoneal metastatic disease. This paper presents the data that supports CRS and HIPEC as a treatment option for CRC patients with PM. These results of treatment are compared and contrasted to the results that can be expected with systemic chemotherapy alone.